Peningkatan Kreativitas Mahasiswa melalui Project Based Learning (PJBL) Berbantuan Generative AI - Linda Dwiyanti; Epritha Kurnia Wati; Gayuh Purbo Ningrum (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
The emergence of Generative Artificial Intelligence (GenAI) requires prospective early childhood education teachers to be able to use it creatively in producing learning products. This study aims to examine the effect of Project Based Learning (PjBL) assisted by Generative Artificial Intelligence (GenAI) on the creativity of Early Childhood Education (PG-PAUD) students in the Artificial Intelligence course. This study employed a quantitative approach with a pre-experimental One Group Pretest-Posttest design, involving 21 students from the 2023 cohort selected through total sampling. Students' creativity data were collected through pretest and posttest, then analyzed using Shapiro-Wilk, Paired Sample t-test, and N-Gain. The results showed an increase in the mean creativity score from 264.71 to 340.52 (p < 0.05), indicating a significant difference between pretest and posttest scores. The N-Gain analysis showed a mean increase of 56.12%, categorized as moderate. These findings indicate that PjBL assisted by GenAI is effective in enhancing the creativity of prospective early childhood education teachers.